Mulato (Brachiaria sp.) - Joao Vendramini; U. Inyang; Brent Sellers; Lynn E. Sollenberger; Maria Silveira (EDIS)
SS-AGR-303, a 4-page fact sheet by J. Vendramini, U. Inyang, B. Sellers, L.E. Sollenberger, and M. Silveira, describes the apomictic hybrid of brachiaragrass with good growing potential for Florida pastures. Includes references. Published by the UF Department of Agronomy, May 2008.